ANALISIS FAKTOR UTAMA DALAM MEMILIH KARTU GSM PRABAYAR DENGAN MENGGUNAKANANALYTICAL HIERARCHY PROCESS - Fatimah Fatimah; Diana Khairani Sofyan; Agus Salim (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
Mobile phonesareone of the productsthat usehightechnology. Thiscardwasonceextremelyrare andexpensivebecauseonlycertaincardsthat can beusedbymobile phone users,butnow manymobilephonecardsthatwe encounter inour liveswith avariety offacilities offered.This is becausemobile phone useis increasinglyrising. Due to the manyexistingcardproductswithcertain advantages,making consumersconfusedinchoosingthe cardto be used.Therefore, it is necessary to doresearch onthe faktorsintoconsideration inthe selection ofthe useofprepaidGSMcard.The method of analysis used is Analytical Hierarchy Process method. This method waschosen because it can be used as a comparison to get priorities in order to determine the bestGSM card later. Bardasarkan findings then some of the faktors that become the criteria forselecting the GSM card is the quality faktor with a weight of 0.49%, the price faktor to thepriority weighting faktor of 0.31% and promos with priority weighting of 19%, while supportingquality faktor is the quality cards, signal quality, coverage and quality. Because without anyquality or range of the signal, the use of prepaid GSM cards will not work even though the priceis cheaper and the rate offered more promo.